2020
DOI: 10.3390/cells9030555
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Stem Cells: Devil or Savior—Looking behind the Scenes of Immunotherapy Failure

Abstract: Although the introduction of immunotherapy has tremendously improved the prognosis of patients with metastatic cancers of different histological origins, some tumors fail to respond or develop resistance. Broadening the clinical efficacy of currently available immunotherapy strategies requires an improved understanding of the biological mechanisms underlying cancer immune escape. Globally, tumor cells evade immune attack using two main strategies: avoiding recognition by immune cells and instigating an immunos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 119 publications
(122 reference statements)
0
25
0
Order By: Relevance
“…The link between stemness and immunosuppression has been further confirmed by a TCGA analysis on 21 solid cancer types, and a negative association between stemness and interferon-/ signaling, and a striking positive association with several immunosuppressive genes, including TGFB1 and CD276 and CD155, two inhibitors of T and natural killer cells, were observed (21). Indeed, CSCs also inhibit immune effector cells thanks to the overexpression of several ICs, which, moreover, exert cell-intrinsic pro-tumoral mechanisms, favoring CSC survival and self-renewal (22). For instance, CSCs from melanoma, ovarian, colorectal and breast cancers express high levels of PD-L1 (23,24), which induces the AKT-dependent expression of the stem-cell markers OCT-4A, Nanog and BMI1 (25).…”
Section: Cancer Stem Cell Immunologymentioning
confidence: 99%
“…The link between stemness and immunosuppression has been further confirmed by a TCGA analysis on 21 solid cancer types, and a negative association between stemness and interferon-/ signaling, and a striking positive association with several immunosuppressive genes, including TGFB1 and CD276 and CD155, two inhibitors of T and natural killer cells, were observed (21). Indeed, CSCs also inhibit immune effector cells thanks to the overexpression of several ICs, which, moreover, exert cell-intrinsic pro-tumoral mechanisms, favoring CSC survival and self-renewal (22). For instance, CSCs from melanoma, ovarian, colorectal and breast cancers express high levels of PD-L1 (23,24), which induces the AKT-dependent expression of the stem-cell markers OCT-4A, Nanog and BMI1 (25).…”
Section: Cancer Stem Cell Immunologymentioning
confidence: 99%
“…Immunoediting comprises all of the immune processes that lead to the control of tumor progression, including an important phase of immunosurveillance [ 134 ]. As a consequence of this tumor elimination phase, a specific subpopulation of CSCs is able to escape immune mechanisms to escape the immune response via, for example, the downregulation of antigen-presenting cells (APCs) [ 135 , 136 ]. As the presentation of tumor antigens from human leukocyte antigen (HLA)-1 to T cells is essential for the recognition phase, the expression of HLA-1 on CSCs may decrease as reported by Di Tomaso et al in a study on glioblastoma CSCs [ 137 ].…”
Section: Tumor Escape and Tamsmentioning
confidence: 99%
“…They drive neoplastic growth and recurrence, even after long latency. Moreover, CSC, due to their ability to modulate and shape immune responses, represent relevant mediators of resistance to immunotherapeutic approaches in cancer patients [28]. At this regard, it has been reported that renal 105 + CSC-EV drive immune-escape by targeting monocyte-derived DC [29].…”
Section: Cancer Stem Cell-evmentioning
confidence: 99%